RASIONALISASI PENGADILAN AGRARIA DI INDONESIA SEBAGAI SOLUSI PENYELESAIAN SENGKETA AGRARIA BERKEADILAN - Imam Koeswahyono; Diah Maharani (Arena Hukum)
The realization of justice in the land sector is a constitutional mandate as stated in article 33 of the 1945 Constitution of Indonesia. However, until now there have been many violations and agrarian conflicts that have occurred which is said to be extraordinary because in them there are structural conflicts and are related to the economic capabilities of certain groups. In order to realize a fair judicial mechanism in overcoming agrarian conflicts, a special institution is needed. This research initiats the Agrarian Court as a special court that has the authority to examine, hear, and decide on agrarian conflicts. The establishment of the Agrarian Court is solely aimed at realizing justice, legal certainty, and benefits in resolving agrarian conflicts and as an independent law enforcement institution. The method used in this study is normative juridical with a statutory and conceptual approach.